(untitled) (Research, Society and Development, 2021)
The Brazil nut is one of the main non-timber forest products in Brazil, but its price fluctuations generate uncertainties and risks for both extractivists and investors. Econometric models or other simpler methods can estimate price changes and indicate the investment attractiveness of the Brazil nut. The objective of the present study was to analyze the risk-return relationship and the export price for both volatility of the Brazil nut over a 15 years period. The historical series of Brazil nut export prices, shelled and unshelled nuts, was evaluated from 2002 to 2016. The geometric growth rate and the variation coefficient indicate the return and risk respectively, associated with its price series. The price volatility of shelled and unshelled Brazil nuts was estimated with the standard deviation of the price series and with generalized models of ARCH (GARCH, EGARCH and TARCH). The shelled or unshelled Brazil nut coefficient increased over 15 years, with a low risk-return ratio. The shelled Brazil nut volatility was lower in the 2002 to 2006, 2007 to 2011 and 2012 to 2016 periods than for the unshelled nut when estimated by the standard deviation method than for the unshelled nut. The shelled Brazil nut price was higher from 2002 to 2016, with low volatility and persistent shocks. The estimate of the shelled and unshelled Brazil nut price volatility was better with the TARCH and the EGARCH models, respectively.